O acesso à educação no sistema prisional e segurança pública: análise da experiência educacional na penitenciária estadual de Francisco Beltrão/Pr - Menegoto, Camila Taís (2019)
The proper study is linked to the research line Society, Knowledge and Education of the Graduate Program in Education/UNIOESTE - Francisco Beltrão Campus. The research addresses access to education for the inmates in Brazil through educational assistance. This is an acquired right guaranteed by the Federal Constitution, the Law of Criminal Execution and Decree Nº. 7.626/2011. The case study was carried out at the Francisco Beltrão/PR State Penitentiary, in order to value the relationship of education in deprivation of liberty spaces, listing the implementation of affirmative actions in Brazil regarding education in prison, knowing its history, evolution of the education system and the treatment it receives. Education is the duty of the State, being a universal right, without disregarding the aspects of Criminal Law, concluding that, in Brazil, the law is being implemented, and in the municipality of Francisco Beltrão is taking effect, achieving good results and demonstrating that the profiles of prisoners in the prison unit are of low income, brown color and low education, but that aims to reach through education, new possibilities of social evolution. Regarding the national prison scenario, it was observed that the Brazilian prison system has serious problems in securing rights, maintaining the social order with effective mechanisms of public security, as well as facing the great problem of vacancy deficit in this system and its correlation with prisoners. Reach 41% of the prison population, resulting in the scrapping of the system, which has more than 812 thousand inmates. Inmates also suffer from non-access to education: 51% of them have incomplete elementary school, only 9% have completed high school and less than 1% have higher education. As a methodological procedure we use the case study, under the qualitative and quantitative approach, and the thematic oral history, in order to highlight concrete facts of the Brazilian prison system.